Calcium Channel Blockers and the Risk for Lung Cancer: A Population-Based Nested Case-Control Study. Issue 5 (May 2019) - Rotshild, Victoria; Azoulay, Laurent; Feldhamer, Ilan; Perlman, Amichai; Glazer, Mendel; Muszkat, Mordechai; Matok, Ilan
Background: It has been suggested that calcium channel blockers (CCBs) may increase the risk of lung cancer; however, current evidence is conflicting and limited.Objective : Investigate the associations between CCB use and lung cancer.Methods: We conducted a population-based nested case-control study. A cohort was formed of patients prescribed their first antihypertensive agent from 2000 to 2014. CCB exposure information was obtained by identification of all prescriptions dispensed during study follow-up. Cases were patients newly diagnosed with lung cancer during follow-up. Each case was matched with 10 controls by age, sex, calendar year of cohort entry, and duration of follow-up. Multivariate conditional logistic regression was used to estimate odds ratios (ORs) with 95% CIs of lung cancer associated with ever use of CCBs.Results: During a median follow-up of 6.2 years, we identified 4174 cases of lung cancer. Ever use of CCBs was associated with an increased risk of lung cancer (adjusted OR = 1.13; 95% CI = 1.06-1.21), when compared with the use of other antihypertensive drugs. A duration-response relation was observed, with the ORs gradually increasing with longer cumulative duration of CCB use (<5 years: OR = 1.12, 95% CI = 1.04-1.20; 5-10 years: OR = 1.22, 95% CI = 1.07-1.40; >10 years: OR = 1.33, 95% CI = 0.90-1.96; P trend < 0.001).Conclusion and Relevance: The results of this large population-based study indicate that the use of CCBs is associated with a modest but significant increase in the risk of lung cancer. This association appeared to increase with longer duration of use.